1992
DOI: 10.1007/bf00596514
|View full text |Cite
|
Sign up to set email alerts
|

Cystic spinal neurilemmoma on magnetic resonance imaging

Abstract: We report a complete cystic change of intradural neurilemmoma at the T12-L1 level. T1-weighted MRI images with gadolinium-DTPA clearly enhanced the thin capsule of the cystic tumour.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0

Year Published

1998
1998
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 5 publications
0
9
0
Order By: Relevance
“…Predominantly cystic schwannomas have been reported throughout the nervous system 19 and at other sites 8 . In a review of the literature, we identified ten cases of cystic schwannoma of the spine 3,6,[9][10][11][12] . Cystic changes are hypothesized to occur due to mucinous degeneration, ischemic necrosis, hemorrhage, and the formation and subsequent coalescence of microcysts.…”
Section: Discussionmentioning
confidence: 99%
“…Predominantly cystic schwannomas have been reported throughout the nervous system 19 and at other sites 8 . In a review of the literature, we identified ten cases of cystic schwannoma of the spine 3,6,[9][10][11][12] . Cystic changes are hypothesized to occur due to mucinous degeneration, ischemic necrosis, hemorrhage, and the formation and subsequent coalescence of microcysts.…”
Section: Discussionmentioning
confidence: 99%
“…Although complete cystic change of neurilemmoma is rare [19], central necrosis or cystic degeneration is sometimes observed [7,10].…”
Section: Discussionmentioning
confidence: 99%
“…Nerve sheath tumours are the most common intradural tumours in the lumbar spinal region 1 . However, intraspinal cystic nerve sheath tumours are uncommon and only approximately eight cases have been reported in the literature to date 2–8 . Neurofibromas and schwannomas are generally not considered in the differential diagnosis of cystic lumbar mass lesions, as these are mostly solid or heterogenous solid tumours.…”
Section: Introductionmentioning
confidence: 99%
“…1 However, intraspinal cystic nerve sheath tumours are uncommon and only approximately eight cases have been reported in the literature to date. [2][3][4][5][6][7][8] Neurofibromas and schwannomas are generally not considered in the differential diagnosis of cystic lumbar mass lesions, as these are mostly solid or heterogenous solid tumours. In such cases, diagnosis of cystic nerve sheath tumours can be difficult.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation